2020
DOI: 10.1002/spp2.1329
|View full text |Cite
|
Sign up to set email alerts
|

Tooth eruption in the Early Cretaceous British mammal Triconodon and description of a new species

Abstract: Triconodon mordax, from the lowest Cretaceous (Berriasian) part of the Purbeck Group, Dorset, is known by an ontogenetic series of specimens that document aspects of tooth eruption and replacement. Based on micro‐computed tomography of four specimens we refer one mandible to a new species, Triconodon averianovi, which differs from T. mordax in having a more slender, curved c; p4 notably low crowned with slender main cusp and smaller accessory cusps; and molars with weak cingula, m4 being notably smaller with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Apart from this, the addition of molars at the posterior end of the molar series was possible without interference with the constrained occlusal system. In Triconodon m4 is formed within the coronoid above the functional tooth row 54 , 60 . This unusual placement could be linked to an increase in tooth count, as the Early Cretaceous Meiconodon and the Late Cretaceous Corviconodon have five lower molars 13 , 60 , 61 .…”
Section: Resultsmentioning
confidence: 99%
“…Apart from this, the addition of molars at the posterior end of the molar series was possible without interference with the constrained occlusal system. In Triconodon m4 is formed within the coronoid above the functional tooth row 54 , 60 . This unusual placement could be linked to an increase in tooth count, as the Early Cretaceous Meiconodon and the Late Cretaceous Corviconodon have five lower molars 13 , 60 , 61 .…”
Section: Resultsmentioning
confidence: 99%
“…All studied taxa are considered as diphyodont (undergoing a single replacement of teeth) on the basis of previous studies of representative dentulous specimens and/or phylogenetic bracketing (4,19,21,50,62). Although additional replacement of certain teeth is known in some eutriconodontan gobiconodontids (63)(64)(65), it has been shown that this is not a generalizable pattern within eutriconodontans (66). Our sample includes the "amphilestid" eutriconodontan Phascolotherium, but gobiconodontids were not represented in our sample.…”
Section: Increment Width Measurementmentioning
confidence: 99%
“…A wide array of dental pathologies have been reported across multiple vertebrate clades, in both extant ( Aalderink et al, 2015 ; Crossley et al, 1998 ; Jett et al, 2017 ; Jones & Franklin, 2006 ; Scarpetta & Bell, 2020 ; Shen et al, 2011 ; Winer et al, 2016b ; Winer, Liong & Verstraete, 2013 ) and extinct taxa ( Candeiro & Tanke, 2008 ; Jäger, Cifelli & Martin, 2020 ; Kirillova, 2009 ; Matthias, McWhinney & Carpenter, 2016 ; Reisz et al, 2011 ; Xing et al, 2013 ). In particular, a category of dental pathologies known as tooth doubling, or connate teeth, is well documented in extant mammalian clades, especially humans ( Agnihotri, Marwah & Goel, 2007 ; Camargo, Aritaa & Watanabe, 2016 ; Cetinbas et al, 2007 ; Ertaş et al, 2014 ; Guler et al, 2013 ; Hülsmann, Bahr & Grohmann, 1997 ; Hunasgi et al, 2017 ; Jain, Yeluri & Munshi, 2014 ; Kamura, 2019 ; Knežević et al, 2002 ; Mahendra et al, 2014 ; Sharma et al, 2015 ; Shokri, Baharvand & Mortazavi, 2013 ; Syed et al, 2016 ; Tasa, 1998 ; Tsesis et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%